Does fire disturbance change insect composition and the frequency of darker phenotypes in a grassland community? - Rocha, Elise Amador; Luz, Fernando Albuquerque; Rossato, Dirleane; Millan, Carolina (Revista Brasileira de Biociências, 2015)
Disturbances like fire can change the composition and frequency of certain phenotypes in the communities due to the selection of some characteristics that would be benefited by habitat change. The present study aimed to evaluate if fire changes a grassland insect community composition and also to test if there is a higher frequency of individuals with darker phenotypes at the community, intra-order (order Orthoptera) and Monoplatina group sp. species levels. Samples were made both in a burned and an unburned area of natural grassland with sweep nets and pitfall traps. Individuals were separated in morphotypes and photographed for posterior analysis of color density with software AxioVision. A total of 253 individuals were collected distributed in 52 morphotypes. Morphotype compositions were significantly different between the two grassland areas. A t-test showed significant differences in the color intensity of individuals between the two areas for all taxonomic levels: the burned area showed a higher number of darker individuals. The results suggest that the increase in the frequency of darker individuals and species in the burned grassland is mainly linked to microevolutive changes, which would be a consequence of differential selection imposed by predators, once darker colors would provide higher protection in the environment darkened by fire.